Russian Contributions to Analytical Chemistry - Zolotov, Yury A. (Springer International Publishing, 2018)
This book offers a unique perspective and novel information on the significant contributions of Russian scientists to analytical chemistry and chemical analysis. Written by the Editor-in-Chief of the Journal of Analytical Chemistry, it discusses various examples of new methods and approaches originating in Russia, such as chromatography, electrothermal atomic absorption spectrometry, Kumakhov X-ray optics, the Spolský effect in fluorescent analysis and important innovations in mass spectrometry, which are already widely used. Other original developments, such as the chromatomembrane and stoichiographic methods, are on their way to international recognition. Tremendous expertise in the analysis of minerals and high-purity and special-purpose substances has accumulated in Russian laboratories, and as such this book appeals to anyone interested in the development of science in Russia; to physicists, chemists, and other specialists dealing with chemical analysis; and to postgraduates and students of chemistry-related disciplines.